Achievement Motivation and Communication Intelligence as Predictors of School Management Effectiveness - Nurlina; Widya Andriyani; M. Syukron Maksum; Wiwin Eko Santoso (Journal of Educational Management Research, 2025)
This study aims to examine the effects of achievement motivation and communication intelligence on school management effectiveness, both partially and simultaneously. A quantitative approach with a causal survey design was employed. The population consisted of all public senior high school teachers in Jambi City, Indonesia, with a sample of 55 teachers selected using probability sampling techniques. Data were collected through structured questionnaires and analyzed using descriptive and inferential statistics, including multiple regression analysis and F-tests, with SPSS version 25. The findings indicate that achievement motivation has a positive and significant effect on school management effectiveness. Similarly, communication intelligence also shows a positive and significant effect on school management effectiveness. Furthermore, achievement motivation and communication intelligence simultaneously exert a highly significant influence on school management effectiveness. These results suggest that enhancing school management effectiveness requires strengthening teachers’ achievement motivation alongside the systematic development of communication intelligence. Such efforts are essential to support more effective, transparent, and accountable school management practices.